(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Childhood obesity has become more prevalent all over the globe. In Thailand, the highest prevalence rate of childhood obesity has been found among primary school students in Northeastern (9.9%), which still exceeds 7% recommended by the WHO. Objective: This study aimed to assess the effectiveness of Food Fit for Fun program with social media used on health literacy and obesity prevention behaviors among senior-primary school students in Nakhon Ratchasima Province, Thailand. Methods: A quasi-experimental was conducted. An experimental and a control group each with 34 participants. A 12-week program was implemented with Health Literacy on dietary and physical activities and social media were used for communication and support. Analysis of the data was performed using t-test while a mean difference and 95%CI were used for determining statistical significance. Results: The senior-primary school children in the experimental group improved their mean difference on health literacy in preventing obesity (10.18; 95% CI: 7.11 to 13.24, p-value <0.001) and dietary and physical activity behaviors (13.44; 95% CI: 6.11 to 20.77, p-value <0.001), compared to the control group. After interventions, the experimental group had a statistically significantly lower mean score on nutritional status (weight for height) (0.26; 95% CI: 0.05 to 0.59, p-value <0.05) and fat percentage (1.71; 95% CI: 0.19 to 3.22, p-value <0.05) than the comparison group. Conclusions: This study provided sustainable evidence on effectiveness of Food Fit for Fun program with the use of social media. This outcome showed that it could improve health literacy in preventing obesity and behavioral modification as well as reduce weight and fat percentage in children.